Modification of Diet to Reduce the Stemness and Tumorigenicity of Murine and Human Intestinal Cells. Issue 19 (31st August 2022) - May, Stephanie; Greenow, Kirsty R.; Higgins, Adam T.; Derrick, Anna V.; Taylor, Elaine; Pan, Pan; Konstantinou, Maria; Nixon, Colin; Wooley, Thomas E.; Sansom, Owen J.; Wang, Li‐Shu; Parry, Lee
Abstract : Scope: Black raspberries (BRBs) have colorectal cancer (CRC) chemo‐preventative effects. As CRC originates from an intestinal stem cell (ISC) this study has investigated the impact of BRBs on normal and mutant ISCs. Methods and results: Mice with an inducible Apc fl mutation in either the ISC ( Lgr5CreER T2 ) or intestinal crypt ( AhCre/VillinCreER T2 ) are fed a control or 10% BRB‐supplemented diet. This study uses immunohistochemistry, gene expression analysis, and organoid culture to evaluate the effect of BRBs on intestinal homeostasis. RNAscope is performed for ISC markers on CRC adjacent normal colonic tissue pre and post BRB intervention from patients. 10% BRB diet has no overt effect on murine intestinal homeostasis, despite a reduced stem cell number. Following Apc ISC deletion, BRB diet extends lifespan and reduces tumor area. In the AhCre model, BRB diet attenuates the "crypt‐progenitor" phenotype and reduces ISC marker gene expression. In ex vivo culture BRBs reduce the self‐renewal capacity of murine and human Apc deficient organoids. Finally, the study observes a reduction in ISC marker gene expression in adjacent normal crypts following introduction of BRBs to the human bowel. Conclusion: BRBs play a role in CRC chemoprevention by protectively regulating the ISC compartment and further supports the use of BRBs in CRC prevention. Abstract : Colorectal cancer (CRC) develops from a mutated intestinal stem cell (ISC). Using CRC/ISC mouse models and patients we demonstrate that black raspberries (BRBs) reduces ISC number and gene expression, inhibits human CRC organoid self‐renewal and extends CRC/ISC mouse survival. Suggesting the link between BRBs and cancer prevention maybe due, at least, in part to an impact on the ISCs. ≈